Crystal Growth, Optical Properties, and Photocatalytic Performances of ZnO‐CuAl2O4 Hybrid Compounds: Theoretical and Experimental Studies. Issue 1 (22nd October 2021) - Naghibi, Sanaz; Basravi, Ali; Tang, Youhong
Abstract: In this study, a two‐step synthesis of the ZnO‐CuAl2 O4 nanocomposite with houseleek‐like grains structures is developed for the first time. The proposed preparation procedure is led to an increase in bandgap energy (Eg ) of the synthesized nanocomposite in comparison with the synthesized ZnO nanoparticles. Theoretically, based on a relation between Eg and the number of surface atoms, the increase in Eg value has been ascribed to the morphology of the synthesized samples. Experimentally, the photocatalytic performance of the synthesized composites, and pristine ZnO and CuAl2 O4 are evaluated by comparing the degradation of methyl orange (MO) solution as a model of azo dye pollutants under UV irradiation. ZnO content and solution pH are selected as variables. Experimental results are showed that acidic pH (≈4) leads to the highest photodegradation performance due to the anionic nature of the MO solution. On the other hand, CuAl2 O4 ‐25%ZnO attained the highest degradation efficiency and high adsorption behavior of the composite is the main reason for this achievement. Abstract : A theoretical and practical study is accomplished on the phase formation, morphological changes, and improvement of the ZnO‐CuAl2 O4 behaviours. The synthesis procedure and mechanisms of grain formation are assessed. Properties of composite materials can be varied by their component, particle size, and morphology, so, the effects of hollow structure and phase component on dye adsorption and photoactivity are investigated.